Penerapan Model Pembelajaran Team Games Tournament berbantuan Dominocard Untuk Meningkatkan Penguasaan Huruf Hiragana Dan Katakana - Lidia Eta Ina Elo; Desak Made Sri Mardani; I Wayan Sadyana (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to determine whether the cooperative learning model of the team games tournament type assisted by domino cards can improve the mastery of class XII BB 1 students of SMA Negeri 4 Singaraja on hiragana and katakana letters. In addition, this study also aims to find out how the students of class XII BB 1 SMA Negeri 4 Singaraja respond to the application of the cooperative learning model of the team games tournament type assisted by domino cards. This type of research is classroom action research. The subjects of this study were 35 students of class XII BB 1 SMA Negeri 4 Singaraja consisting of 17 male students and 18 female students. This study used several methods in collecting data, namely: test methods, observation methods, and questionnaires/questions. As for the results of this study, namely: the percentage of student learning outcomes in the post-test cycle I and post-test cycle II were 63% and 100%. The increase in the classical post-test results of students indicates that the cooperative learning model of the team games tournament type assisted by domino cards can improve the mastery of hiragana and katakana letters for class XII BB 1 SMA Negeri 4 Singaraja. This was also supported by very positive student responses to the application of the cooperative learning model of the team games tournament type assisted by domino cards. In the observation results it was also seen that students began to experience an increase in both learning outcomes and learning motivation.